Cinza de biomassa florestal no cultivo de olerícolas e plantas ornamentais - Andrade, Edna Aparecida de (2024)
This study evaluated the potential of using forest biomass ash as a fertilizer in various forms (top dressing, fertigation and granulated), as well as its residual effect on vegetable crops [lettuce (Lactuca sativa L.), onion (Allium cepa L.), melon (Cucumis melo L.), strawberry (Fragraria x Ananassa Ducho) and ornamental plants [(stone rose (Echeveria Elegans Rose) and Christmas cactus (Schlumbergera Truncata (Haworth) Moran)]. The experiments were conducted in a protected environment in Santa Tereza do Oeste, PR. The doses of forest biomass ash evaluated were equivalent to 0, 5, 10, 15 and 20 t ha-1. The trials were conducted in pots suitable for each crop (10, 3, 1 and 0.5 dm³) filled with substrate (a mixture of clay soil, sand and carbonized rice husks). Phytotechnical characteristics such as fresh fruit mass production, dry mass production of the aerial part and bulbs and number of flowers per plant were evaluated according to the crop studied. The averages of the data obtained in the experiments were evaluated using a statistical program (Statistica) and subjected to analysis of variance (ANOVA), followed by Tukey's multiple mean comparison test with 5% significance. The ash caused an increase in productivity in all the crops evaluated in all forms of application. In the crops in which the residual effect of ash applied via fertigation, granules and top dressing were evaluated, there was a positive effect on the increase in productivity. The recommended doses (maximum economic efficiency) ranged from 1.2 to 9 t ha-1 of ash, depending on the crop and method of application, with an average of 5.4 t ha-1. Forest biomass ash showed high potential for use as a fertilizer and corrective in growing vegetables.